2012
DOI: 10.1155/2012/137037
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pathogenesis-Related Proteins in the Tomato-Rhizoctonia solani Interaction

Abstract: Rhizoctonia solani is one of the most destructive pathogens causing foot rot disease on tomato. In this study, the molecular and cellular changes of a partially resistant (Sunny 6066) and a susceptible (Rio Grande) tomato cultivar after infection with necrotrophic soil-borne fungus R. solani were compared. The expression of defense-related genes such as chitinase (LOC544149) and peroxidase (CEVI-1) in infected tomato cultivars was investigated using semiquantitative reverse transcription-polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
(34 reference statements)
1
30
0
Order By: Relevance
“…RONS also play an important role in host plant resistance to microbial infection (Mittler, ; Kotchoni & Gachomo, ; Taheri & Tarighi, ). However, there are only two reports of CP inducing host resistance to plant pathogenic fungi (Table ).…”
Section: Cold Plasma For Postharvest Disease Controlmentioning
confidence: 99%
“…RONS also play an important role in host plant resistance to microbial infection (Mittler, ; Kotchoni & Gachomo, ; Taheri & Tarighi, ). However, there are only two reports of CP inducing host resistance to plant pathogenic fungi (Table ).…”
Section: Cold Plasma For Postharvest Disease Controlmentioning
confidence: 99%
“…The β-1, 3-glucanase (PR-2) and chitinase 4,8 and 11) are known to be more efficient against several bacterial and fungal pathogens (van Loon et al, 2006;Kocal et al, 2008). Also, or peroxidases are key enzymes in the cell-wall-building process, and it has been suggested that extracellular peroxidases would increase resistance in various plant species against phytopathogens (Cavalcanti et al, 2006;Taheri & Taheri, 2012). As a result of plant-microbe interaction, plants trigger molecular mechanisms that pass on to the rapid production of the high amount of reactive oxygen species (ROS) (De Leon & Montesano, 2013;Bolouri Moghaddam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar result was obtained by Reuveni et al (1992) while estimating peroxidase activity in muskmelon to Pseudoperonospora cubensis where he found that the peroxidase activity was lower in highly susceptible line, intermediate in the susceptible and high in resistant cultivars. Taheri and Tarighi (2012) reported that more peroxidase activity was found in partially resistant cultivar of tomato as compared to susceptible cultivar, their findings suggest the involvement of peroxidase in defense responses of tomato plants against R. solani as a destructive pathogen.…”
Section: Resultsmentioning
confidence: 93%